Building Employee Health Monitoring Tool Using IoT Oximeter in Palm Industry - Helmi Wardah Nasution; Dwi Ris Hasanah; Rayandra Asyhar (University of Respati Yogyakarta, Indonesia, 2025)
Ensuring employee health and safety is a critical concern in the palm oil industry, where physically demanding environments can pose significant risks. Traditional health monitoring methods often lack real-time data collection and prompt intervention capabilities, creating gaps in maintaining occupational health standards. This paper addresses these challenges by presenting the design and implementation of an Internet of Things (IoT)–based oximeter prototype tailored to the needs of the palm oil industry. The system leverages the Blynk IoT platform to enable continuous monitoring of employees' oxygen saturation levels (SpO2) and heart rates in real time. By integrating sensor-based data collection with a user-friendly interface, the prototype facilitates immediate access to vital health metrics and sends alerts for abnormalities. A simulated palm oil plantation environment was used to evaluate the system, demonstrating its effectiveness in delivering accurate health measurements and timely notifications. Results indicate that the IoT-based oximeter significantly enhances employee health monitoring by addressing the limitations of traditional methods, promoting proactive health management, and enabling timely interventions. This innovation not only improves workplace safety but also fosters a culture of health awareness among employees and is a valuable tool for occupational health monitoring in the palm oil industry.